The effect between metabolic syndrome and life expectancy after cancer diagnosis: Catalan cohort study - Tomàs López-Jiménez; Oleguer Plana-Ripoll; Talita Duarte-Salles; Anna Palomar-Cros; Diana Puente (BMC Public Health)
Abstract This study examines remaining life expectancy (RLE) after a cancer diagnosis, focusing on age, sex, cancer type, and metabolic syndrome (MS) components, using data from the SIDIAP database in Catalonia (2006–2017). RLE was analyzed for 13 cancer types, stratified by sex and MS components. The cohort study includes 183,364 individuals followed from diagnosis until death, transfer, or study end (December 2017). RLE at age 68 (median diagnosis age) was calculated based on MS components (0, 1, 2, and ≥ 3). Men aged 68 with 0 MS components had an RLE of 13.2 years, compared to 8.9 years for those with ≥ 3 MS. Women had an RLE of 15.9 years with 0 MS components versus 11.4 years with ≥ 3 MS. RLE varied by cancer type, with the highest RLE in men seen in prostate cancer and in women in non-Hodgkin lymphoma. The lowest RLE for both sexes was in pancreatic cancer. The largest differences between 0 and ≥ 3 MS components were observed in non-Hodgkin lymphoma and the smallest in pancreatic cancer. Increased MS components were associated with reduced RLE in at least 8 cancer types for men and 9 for women. Prevention strategies targeting MS components could increase RLE in cancer patients.